Combustion instability - Natanzon, M. S. (American Institute of Aeronautics and Astronautics, 1999)
Annotation This book?much of it formerly classified material--is a clear exposition of much of the theoretical work on combustion instabilities, performed in support of the Soviet liquid rocket program during its most vigorous period. While there are similarities between Western and Eastern works, there are many distinct differences. The author was one of the small group of Soviet theorists actively engaged in all of the Soviet liquid rocket programs. His development of the field is firmly grounded in fundamental ideas, and progresses to applications of a general sort. One chapter is new since the original Russian edition, covering both theory and experiment for bifurcations of dynamical behavior in liquid rocket chambers.
Originally published in 1986 by Mashinostroenie, Moscow.
Keywords: Combustion.; elektronické knihy; electronic books